Penerapan Teori Self-Care Orem Pada Asuhan Keperawatan Pasien dengan Osteoartritis Genu Bilateral - Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
Osteoarthritis of the knee (OA genu) is an idiopathic OA, which is characterized by degeneration of knee cartilage that affect the occurrence of disability. Due to disability they experienced, patient difficulty to perform self-care. Related to this, the role of nurses are needed in the provision of nursing care to approach the theory of Orem self care in patients with osteoarthritis genu. Nursing care methods with Orem's self care approach are applied to Mrs. MS is 52 years old with Bilateral OA Genu. The purpose of writing is to get real experience in providing nursing care for patients with bilateral OA Genu. The results obtained are complaints of controlled pain, optimal mobility achieved, patients can avoid the risk of falls and infection. The conclusion is that nursing care methods using Orem's self-care theory approach are effective to apply to patients with musculoskeletal system disorders, especially in cases of osteoarthritis because patients with these cases have self-care problems.